2020
DOI: 10.3390/nano10122519
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Single Molecules Using Stochastic Resonance of Bistable Oligomers

Abstract: Ultra-sensitive elements for nanoscale devices capable of detecting single molecules are in demand for many important applications. It is generally accepted that the inevitable stochastic disturbance of a sensing element by its surroundings will limit detection at the molecular level. However, a phenomenon exists (stochastic resonance) in which the environmental noise acts abnormally: it amplifies, rather than distorts, a weak signal. Stochastic resonance is inherent in non-linear bistable systems with critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Following Kramer's rate approximation with the collision time for random perturbations ranging from 0.1-10 ps, one can roughly www.videleaf.com estimate the bistability barrier of the oligo-PF-5 spring as 10-15 kBT. Interestingly, the bistability barrier of the oligo-PF-5 spring turned out to be roughly equal to the same value as that for the oligomeric Euler arch described in [42,43]. Even though the reasons for the bistability of the oligo-PF-5 spring and the oligomeric Euler arch were different, the bistability barriers of both bistable oligomeric systems were about ten times larger than the characteristic scale of thermal fluctuations, kBT.…”
Section: Bistable Dynamics Of Oligo-pf-5 Springmentioning
confidence: 68%
See 2 more Smart Citations
“…Following Kramer's rate approximation with the collision time for random perturbations ranging from 0.1-10 ps, one can roughly www.videleaf.com estimate the bistability barrier of the oligo-PF-5 spring as 10-15 kBT. Interestingly, the bistability barrier of the oligo-PF-5 spring turned out to be roughly equal to the same value as that for the oligomeric Euler arch described in [42,43]. Even though the reasons for the bistability of the oligo-PF-5 spring and the oligomeric Euler arch were different, the bistability barriers of both bistable oligomeric systems were about ten times larger than the characteristic scale of thermal fluctuations, kBT.…”
Section: Bistable Dynamics Of Oligo-pf-5 Springmentioning
confidence: 68%
“…Based on these lifetimes and following Kramer's rate approximation with the collision time ranging from 0.1-10 ps, we estimated the bistability barriers of both springs as 10-15 𝑘 𝐵 𝑇. It is noteworthy that the time scales of spontaneous vibrations of the oligo-PF-5 and the oligo-PF-7 springs and their bistability barriers were approximately the same as those of the oligomeric Euler arch described in [42,43]. The bistability barriers of short PF springs appear to be high enough to separate the two states against the thermal noise; on the other hand, the same barriers allowed activation of the transitions between the two states by energetically enriched thermal fluctuations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…SR theory was proposed in 1981 to explain the glacier problem [ 1 ]. For many domains, SR can be used and has good performance [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In the aspect of feature extraction and signal enhancement of mechanical signals, SR is used more and more because it is different from other denoising methods [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article focuses on nanoscale molecular structures whose dynamic prototypes are the textbook bistable mechanical systems known as Euler arches (a beautiful but simple example of a bistable machine which is composed of two rigid rods joined by a hinge with an elastic spring) [27][28][29] and Duffing oscillators [30,31]. In particular, using molecular dynamics simulations, it was found that the long-term conformational dynamics of short rod-shaped thermosensitive oligomers were similar to the bistable dynamics of a Euler arch [29,32,33], while particular oligomers of a helical form stabilized via weak intermolecular interactions could behave as bistable Duffing oscillators [29,34].…”
Section: Introductionmentioning
confidence: 99%